2011
DOI: 10.1590/s0104-11692011000700015
|View full text |Cite
|
Sign up to set email alerts
|

Factores sociales para el uso de alcohol en adolescentes y jóvenes

Abstract: Esta investigación analiza factores sociales de riesgo y de protección para el consumo excesivo de alcohol a partir de los datos de la Encuesta Nacional sobre prevalencias de consumo de sustancias psicoactivas, en 2008, en la población de jóvenes argentinos de 16 a 24 años. Se realizó análisis bivariado y multivariado. Se observó como factores de riesgo: la edad de inicio (el menor edad tiene mayor riesgo), la región Pampeana, Noroeste y Noreste, el género masculino y el provenir de hogares con necesidades bás… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
18

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 16 publications
(33 reference statements)
2
5
0
18
Order By: Relevance
“…These studies showed a relationship between alcohol consumption and male gender, and increase in age. [24][25] However, there are studies that show a higher prevalence of consumption among female adolescents, as shown in studies conducted in Brasil. [26][27][28] Differences between Brazilian studies and the present study might be explained by the diversity in location, since Portugal, where the present study was conducted, is very traditional, with risk behaviors more associated with the male gender.…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed a relationship between alcohol consumption and male gender, and increase in age. [24][25] However, there are studies that show a higher prevalence of consumption among female adolescents, as shown in studies conducted in Brasil. [26][27][28] Differences between Brazilian studies and the present study might be explained by the diversity in location, since Portugal, where the present study was conducted, is very traditional, with risk behaviors more associated with the male gender.…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, ambos apresentam grande prevalência nessa etapa da vida e, portanto, estão presentes de forma significativa no ambiente escolar, prejudicando o desempenho acadêmico dos envolvidos, além de aparecem frequentemente relacionados a um dos grandes problemas de saúde pública: a violência de um modo geral 2,4,8,12,13 . São, ainda, fenômenos que influenciam e são influenciados pelos grupos de iguais, uma vez que tanto o bullying como o uso de substâncias psicoativas costumam ser situações que o jovem vivencia junto com amigos, seja pela simples oferta ou pela função integradora que o envolvimento nesses comportamentos pode representar 16,17 . Uma compreensão mais profunda destes fenômenos e da relação entre eles, necessária na promoção de cuidados dirigidos à prevenção ou ao manejo de situações típicas, depende ainda de uma sistematização das evidências disponí-veis que reflitam em que medida bullying e uso de substâncias estão associados e se esta relação se modifica segundo os diferentes papéis sociais identificados entre os envolvidos em bullying (ví-tima, vítima-agressor ou agressor).…”
Section: Introductionunclassified
“…Investigaciones evidencian que el patrón de consumo a nivel internacional en los jóvenes es hasta estar ebrios ; dentro de los mismos estudios se ha demostrado una alta prevalencia de ebriedad, así como una tendencia a estar cada vez más ebrios , término que hoy en día usan como binge drinking consumo episódico excesivo de alcohol) 5 .…”
Section: Introductionunclassified